Mechanisms of Activation of Receptor Tyrosine Kinases: Monomers or Dimers - Ichiro N. Maruyama (Cells, 2014)
Receptor tyrosine kinases (RTKs) play essential roles in cellular processes, including metabolism, cell-cycle control, survival, proliferation, motility and differentiation. RTKs are all synthesized as single-pass transmembrane proteins and bind polypeptide ligands, mainly growth factors. It has long been thought that all RTKs, except for the insulin receptor (IR) family, are activated by ligand-induced dimerization of the receptors. An increasing number of diverse studies, however, indicate that RTKs, previously thought to exist as monomers, are present as pre-formed, yet inactive, dimers prior to ligand binding. The non-covalently associated dimeric structures are reminiscent of those of the IR family, which has a disulfide-linked dimeric structure. Furthermore, recent progress in structural studies has provided insight into the underpinnings of conformational changes during the activation of RTKs. In this review, I discuss two mutually exclusive models for the mechanisms of activation of the epidermal growth factor receptor, the neurotrophin receptor and IR families, based on these new insights.